2020
DOI: 10.1007/s00415-020-10108-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated neurological syndromes in SARS-CoV-2-infected patients

Abstract: Background Evidence of immune-mediated neurological syndromes associated with the severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection is limited. We therefore investigated clinical, serological and CSF features of coronavirus disease 2019 (COVID-19) patients with neurological manifestations. Methods Consecutive COVID-19 patients with neurological manifestations other than isolated anosmia and/or non-severe headache, and with no previous neurological or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
208
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(223 citation statements)
references
References 15 publications
3
208
1
5
Order By: Relevance
“…To date, five cohort studies provided a prevalence of neurological manifestations in a total of 2533 COVID-19 patients [2] , [3] , [4] , [5] , [6] ( Table 1 ). This prevalence ranged from 4.3 to 73.0% depending on which symptoms are considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, five cohort studies provided a prevalence of neurological manifestations in a total of 2533 COVID-19 patients [2] , [3] , [4] , [5] , [6] ( Table 1 ). This prevalence ranged from 4.3 to 73.0% depending on which symptoms are considered.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired consciousness was one of the most common neurological symptoms in cohort studies, reported in 1.8 to 21.3% of hospitalized COVID-19 patients [2] , [3] , [4] , [5] , [6] ( Table 1 ), up to 69% in severe patients needing intensive care management [11] . Disorder of consciousness occurred with a mean time of onset of 8 to 9 days in the evolution of COVID-19, and was associated with severe infection, older age, higher creatine kinase levels, lower lymphocyte counts and higher blood urea nitrogen [2] , [3] .…”
Section: Resultsmentioning
confidence: 99%
“…No studies have reported the prevalence of cognitive impairment among survivors of COVID-19, so extrapolation from other severe illnesses is necessary. Cognitive impairment comparable to mild Alzheimer's dementia has been estimated to occur in 25% of survivors of critical illness [77] and may be associated with prolonged delirium [78,79], severe hypoxaemia [78][79][80][81], early neurological manifestations [82], and duration of sedative-analgesia administration [80,83]. COVID-19 patients have risk factors for cognitive deficits [84], but there is no empirical evidence that cognitive deficits are as frequent among COVID-19 survivors or that interventions can improve cognitive outcomes [85,86].…”
Section: Cognitive Outcomesmentioning
confidence: 99%
“…Autoimmune panel negative on CSF and serum for anti LGI1, CASPR2, NMDAR, GABAB1R, GABAB2R, AMPAR1, AMPAR2, Hu, Yo, Ri, CV2, amphiphysin CS Slight disability, unable to perform all previous activities 4 Guilmot et al. ( Guilmot et al., 2020 ) 80, M Mild Short term memory disturbances, seizure, visual hallucinations, anxiety Not applicable Generalized slowing Normal 9 cells/mm 3 ; 46 ​mg/dl Negative CSF PCR for viral agents negative. Positive OCB.…”
Section: Literature Review: Resultsmentioning
confidence: 99%